2023
DOI: 10.3390/jcm12124022
|View full text |Cite
|
Sign up to set email alerts
|

How May Longer Console Times Influence Outcomes after Robot-Assisted Radical Prostatectomy (RARP)?

Abstract: Longer operating time in radical prostatectomy may increase the risk of perioperative complications. Various factors such as cancer extent, the procedure’s level of difficulty, habitus and previous surgeries may lengthen robot-assisted radical prostatectomy (RARP) and therefore compromise outcomes. Objective: this study investigates the influence of operating time on outcomes after RARP in real life settings in a monocentric single surgeon study. Methods: a total of 500 sequential patients who were operated on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Briganti et al [ 13 ] reasoned that if a PLND is indicated, then it should be extended, and in low-risk PCa, a staging ePLND might be spared. In our practice, we perform pelvic lymph adenectomy in all patients to prevent the risk of under-staging or under-grading due to the high rate of tumor misclassification from referring centers [ 14 ]. We abstained from further discrimination between standard and extended since it did not result in any clinical implications in our cohort, in which all patients received an extended PLND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briganti et al [ 13 ] reasoned that if a PLND is indicated, then it should be extended, and in low-risk PCa, a staging ePLND might be spared. In our practice, we perform pelvic lymph adenectomy in all patients to prevent the risk of under-staging or under-grading due to the high rate of tumor misclassification from referring centers [ 14 ]. We abstained from further discrimination between standard and extended since it did not result in any clinical implications in our cohort, in which all patients received an extended PLND.…”
Section: Discussionmentioning
confidence: 99%
“…Yet none of them had concurrent lymphocele. Nonetheless thromboembolic events are linked to longer OR-time [ 14 ], the least mentioned it prolonged by extended lymph adenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, longer operative time during RARP is reported to be associated with longer hospitalization, longer catheterization, and higher likelihood of adverse events. This is why we believe that anything that can be done for reducing the operating time should be welcome ( 19 ).…”
Section: Discussionmentioning
confidence: 99%